A case of methaemoglobinaemia. Issue 2 (June 1993) - Dudley, M J; Solomon, T
Abstract : Methaemoglobinaemia is rare but should be considered in cases of cyanosis unresponsive to oxygen therapy. An example of this is given involving the accidental ingestion of Amyl Nitrite.